Catalyst for hydracrylic acid dehydration reaction and preparation method thereof
By molding the hydroxyapatite powder into a molded body with a specific particle size range and controlling the P value of the catalyst, the problem of low catalyst yield in the prior art is solved, and the catalyst effect with high yield and long life is achieved.
Patent Information
- Application Number
- CN202480003442.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2024-06-07
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, when synthesizing acrylic acid through dehydration reaction using hydroxyapatite catalysts, the yield is lower, especially the catalysts replaced by Ca by Sr, and the yield is even lower.
The catalyst was prepared by molding the hydroxyapatite powder into a molded body with primary particles and controlling its volume average particle size between 15 μm and 150 μm, and using the equation P=A*B/C, the P value was calculated between 3.5 and 19.
High reaction yield and selectivity are achieved, and the catalyst has excellent lifetime characteristics, solving the problems of short and low catalyst lifetime in the prior art.
Smart Images

Figure BDA0005247330740000151
Abstract
Description
Technical Field
[0001] The present disclosure relates to a catalyst for dehydration reaction of hydroxypropionic acid and its derivatives and a preparation method thereof.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application is based on and claims priority from Korean Patent Application No. 10-2023-0081445 filed on June 23, 2023, the disclosure of which is incorporated herein by reference in its entirety. Background Art
[0004] Acrylic acid is generally synthesized by a two-step oxidation reaction of propylene as a petroleum-derived raw material. However, due to the rapid rise in crude oil prices and concerns about future depletion, research is being conducted to obtain unsaturated carboxylic acids such as acrylic acid from biomass raw materials.
[0005] Lactic acid can be produced on a large scale from starch by fermentation, and acrylic acid can be produced by dehydration reaction of lactic acid. In the dehydration reaction of lactic acid, metal phosphates, metal sulfates or zeolite catalysts are mainly used. Among them, metal phosphates are being widely studied, but they have the problem of low yield of acrylic acid.
[0006] Specifically, International Patent Publication No. WO2011 / 052178 proposes a synthesis method using hydroxyapatite (Ca 10 (PO4)6(OH)2) or Sr 10 (PO4)6(OH)2 is used as a catalyst to synthesize unsaturated carboxylic acid or its derivative from hydroxycarboxylic acid or its derivative by dehydration reaction. However, when hydroxyapatite is used to synthesize acrylic acid from lactic acid, the yield of acrylic acid is about 50% to 70%, and when Sr in which Ca in hydroxyapatite is replaced by Sr is used, the yield of acrylic acid is about 50% to 70%. 10 In the case of (PO4)6(OH)2, the yield of acrylic acid was even lower, at about 30%.
[0007] Therefore, there is a need to develop a method and a catalyst capable of synthesizing an unsaturated carboxylic acid such as acrylic acid or an ester thereof in high yield. Summary of the invention
[0008] Technical issues
[0009] The invention provides a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives.
[0010] The present invention also provides a method for preparing the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives.
[0011] Technical Solution
[0012] The present invention provides a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives, the catalyst comprising a molded body in which hydroxyapatite primary particles are aggregated, wherein the volume average particle size of the primary particles is 15 μm to 150 μm; and the P value represented by the following equation 1 is 3.5 to 19.
[0013] [Equation 1]
[0014] P=A*B / C
[0015] In equation 1, A represents the volume average particle size (μm) of the powder, B represents the crushing strength (N), and C represents the specific surface area (m 2 / g) value.
[0016] According to one embodiment, the primary particles may have a particle size of about 25 μm to about 100 μm.
[0017] According to one embodiment, the content of the alkali metal in the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 3 wt % to about 8 wt %.
[0018] According to one embodiment, the alkali metal may be sodium or potassium.
[0019] According to one embodiment, the apparent density of the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 0.8 g / cm 3 To about 1.0g / cm 3 .
[0020] According to one embodiment, the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may have a crush strength value of about 6N to about 20N.
[0021] According to one embodiment, the specific surface area value of the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 50 m 2 / g to 90m 2 / g.
[0022] At the same time, the present invention provides a method for preparing the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives, which method includes the following steps: preparing a slurry by introducing 1 to 50 parts by weight of a binder relative to 100 parts by weight of hydroxyapatite; producing a molded body by molding the slurry; and drying the molded body.
[0023] According to one embodiment, the binder may include 0.1 parts by weight to 10 parts by weight of isopropyl alcohol relative to 100 parts by weight of hydroxyapatite.
[0024] Meanwhile, the present invention provides a method for preparing acrylic acid, which comprises the step of carrying out a dehydration reaction of a hydroxycarboxylic acid or a derivative thereof in the presence of the above catalyst.
[0025] As used in the present specification, the terms “first”, “second”, etc. are used to describe various components, and these terms are only used to distinguish a certain component from other components.
[0026] Furthermore, the terms used in the present specification are only used to explain exemplary embodiments and are not intended to limit the present invention.
[0027] Unless differently expressed in the context, a singular expression may include a plural expression.
[0028] It must be understood that the terms "including", "equipped with" or "having" in this specification are only used to explain the adopted features, numbers, steps, components or their combinations, and do not exclude the possibility of one or more different features, numbers, steps, components, their combinations or additions.
[0029] Furthermore, in this specification, when it is mentioned that a layer or an element is formed “on” or “over” a layer or an element, this means that each layer or element is directly formed on the layer or element, or other layers or elements may be additionally formed between layers, objects, or substrates.
[0030] The present invention can be modified in various ways and has various forms, and specific embodiments will be described and explained in detail below. However, it should be understood that this description is not intended to limit the present invention to the specific forms disclosed, but rather, is intended to cover all modifications, equivalents and substitutes that fall within the concept and scope of the present invention.
[0031] In the present specification, the hydroxypropionic acid derivative refers to a group of compounds including hydroxypropionic acid and its derivatives, which are carboxylic acids having 3 carbon atoms in the main chain, one of which is substituted with a hydroxyl group.
[0032] In addition, the dehydration reaction of hydroxypropionic acid and its derivatives refers to a reaction in which a hydroxyl group and a hydrogen bonded to an adjacent carbon in the corresponding compound are eliminated to form a carbon-carbon unsaturated double bond.
[0033] Hereinafter, the present invention will be described in detail.
[0034] According to one aspect of the present disclosure, a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives is provided, the catalyst comprising a molded body in which hydroxyapatite primary particles are aggregated, wherein the volume average particle size of the primary particles is 15 μm to 150 μm; and the P value represented by the following equation 1 is 3.5 to 19.
[0035] [Equation 1]
[0036] P=A*B / C
[0037] In equation 1, A represents the volume average particle size (μm) of the powder, B represents the crushing strength (N), and C represents the specific surface area (m 2 / g) value.
[0038] Apatite compounds refer to compounds having an apatite structure, but generally refer to compounds comprising calcium and phosphorus and having the chemical formula Ca A (PO4) B -X represents a calcium phosphate series compound.
[0039] Hydroxyapatite refers to a compound in which X in the chemical formula is a hydroxyl group. Due to its unique structure and the presence of acid sites, this hydroxyapatite compound can be used as a catalyst in the dehydration reaction of hydroxypropionic acid and its derivatives for producing unsaturated carboxylic acids.
[0040] However, when these calcium phosphate series compounds are used as conventional hydroxyapatite single-phase catalysts, the yield of the dehydration reaction is not high, and in particular, the yield decreases significantly with the lapse of reaction time, and the life span thereof is very short, so there is a problem of low processability.
[0041] The inventors of the present invention have discovered that in a method for preparing acrylic acid and the like by dehydration reaction of hydroxypropionic acid and its derivatives using hydroxyapatite as a catalyst, when hydroxyapatite powder is molded and the molded body is used as a catalyst, if the particle size of the hydroxyapatite powder used for molding is controlled within a predetermined range, a catalyst having very excellent life characteristics while having high reaction yield and selectivity can be provided, thereby completing the present invention.
[0042] According to one embodiment of the present disclosure, a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives is provided, the catalyst comprising a molded body in which hydroxyapatite primary particles are aggregated, wherein the volume average particle size of the primary particles is 15 μm to 150 μm; and the P value represented by the following equation 1 is 3.5 to 19.
[0043] [Equation 1]
[0044] P=A*B / C
[0045] In equation 1, A represents the volume average particle size (μm) of the powder, B represents the crushing strength (N), and C represents the specific surface area (m 2 / g) value.
[0046] According to one embodiment, the volume average particle diameter of the primary particles may be 15 μm to 150 μm.
[0047] In other words, a molded body prepared by molding hydroxyapatite powder is used as a catalyst instead of using hydroxyapatite in a crystalline or powdered form as a catalyst. In this regard, the particle size of the powder constituting the molded body, i.e., the primary particles, may be about 15 μm to about 150 μm, or about 15 μm or more, or about 17 μm or more, or about 20 μm or more, or about 23 μm or more, or about 25 μm or more, and about 150 μm or less, or about 140 μm or less, or about 130 μm or less, or about 120 μm or less, or about 110 μm or less, or about 100 μm or less.
[0048] When the size of the primary particles, i.e., hydroxyapatite powder, used to prepare the molded catalyst is too small, the density of the powder in the catalyst molded body increases, which tends to increase the physical strength. However, this characteristic may cause the problem of a reduction in the specific surface area required for the dehydration reaction. When the size of the primary particles, i.e., hydroxyapatite powder, is too large, the strength of the catalyst molded body is weak, so it cannot be molded, and there may be problems of side reactions caused by catalyst breakage in the dehydration reaction and increased pressure difference in the reactor.
[0049] According to one embodiment, the content of the alkali metal in the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 3 wt % to about 8 wt %.
[0050] In the hydroxyapatite compound used as a catalyst for preparing an unsaturated carboxylic acid or its derivative, the content of alkali metal in the compound may affect the selectivity in the preparation of the unsaturated carboxylic acid and its derivative. Specifically, when the content of alkali metal in the catalyst, especially on the catalyst surface, is low, the selectivity decreases, but when the content of alkali metal is high, the selectivity can be kept high.
[0051] Meanwhile, the molar ratio of calcium to phosphorus (Ca / P molar ratio) on the catalyst surface affects the yield of the product, that is, the conversion rate of acrylic acid. When the Ca / P molar ratio is too high or too low, the yield may be reduced.
[0052] However, in the preparation of unsaturated carboxylic acids or derivatives thereof, selectivity and conversion rate show a trade-off relationship, and therefore, it is difficult to improve both the selectivity and conversion rate.
[0053] According to one embodiment of the present disclosure, the content of alkali metal in the catalyst can maintain a high level of alkali metal ratio of about 3 wt % to about 8 wt %, and the alkali metal content on the catalyst surface can also be maintained at a high level. Therefore, when preparing unsaturated carboxylic acids and derivatives thereof, by increasing the content of alkali metal on the catalyst surface and controlling the mixing ratio of Ca and P, the selectivity and conversion rate can be further improved.
[0054] Specifically, in a catalyst according to one embodiment, the molar ratio of calcium to phosphorus (P) on the catalyst surface (molar ratio of Ca / P) may be about 1.0 or more and about 1.2 or less, more specifically, about 1.0 or more, or about 1.05 or more, or about 1.1 or more, and about 1.2 or less, or less than about 1.2, or about 1.15 or less.
[0055] In addition, the total molar ratio of calcium and alkali metals to phosphorus on the catalyst surface (molar ratio of (Ca+M) / P) can be about 1.2 or more and about 1.6 or less, more specifically, about 1.2 or more, or about 1.3 or more, and about 1.6 or less, or less than about 1.6, or about 1.5 or less, or about 1.45 or less, or about 1.4 or less.
[0056] The catalyst may have a high content of alkali metals on the catalyst surface of about 4 wt % or more and about 8 wt % or less, based on the total weight of the elements present on the catalyst surface, more specifically, about 4 wt % or more, or about 5 wt % or more, or about 6 wt % or more, or about 6.5 wt % or more, and about 8 wt % or less, or about 7.5 wt % or less, or about 7 wt % or less.
[0057] Meanwhile, in the present disclosure, the element content (at %) based on the atomic weight of elements including phosphorus, calcium, and alkali metals on the catalyst surface may be measured through XPS analysis.
[0058] According to the calcium (Ca) content (at%), phosphorus (P) element content (at%) and alkali metal (M) element content calculated by XPS analysis, the molar ratio of calcium to phosphorus on the catalyst surface can be obtained by the ratio of Ca element content (Ca at%) / P element content (P at%). In addition, the total molar ratio of calcium and alkali metal to phosphorus can be obtained by the ratio of (Ca at%+M at%) / (Pat%).
[0059] In addition, the content (weight %, wt %) of the alkali metal present on the catalyst surface can be calculated based on the element content (at %) calculated above.
[0060] As described above, when preparing unsaturated carboxylic acids or their derivatives, the selectivity and conversion rate can be further improved by controlling the content ratio of phosphorus, calcium and alkali metal on the catalyst surface and the content of the above elements in the catalyst.
[0061] Specifically, the content of alkali metal in the catalyst can be about 3 wt % or more and about 5 wt % or less, based on the total weight of the catalyst. More specifically, the content of alkali metal in the catalyst can be about 3 wt % or more, or about 3.2 wt % or more, and about 5 wt % or less, or about 4.5 wt % or less, about 4 wt % or less, or about 3.7 wt % based on the total weight of the catalyst.
[0062] In addition, the molar ratio of calcium to phosphorus in the catalyst (Ca / P molar ratio) can be about 1.3 or more and about 1.5 or less, more specifically, about 1.3 or more, or about 1.35 or more, or about 1.4 or more, and about 1.5 or less, or about 1.45 or less.
[0063] The total molar ratio of calcium and alkali metal (M) to phosphorus in the catalyst (molar ratio of (Ca+M) / P) can be about 1.2 or more and about 2 or less, more specifically, about 1.2 or more, or about 1.5 or more, or about 1.6 or more, or about 1.65 or more, or about 1.7 or more, and about 2 or less, or about 1.9 or less, about 1.8 or less, or about 1.75 or less.
[0064] Meanwhile, in the present disclosure, the contents of elements including phosphorus, calcium, and alkali metals in the catalyst may be calculated by inductively coupled plasma mass spectrometry (ICP), more specifically, inductively coupled plasma optical emission spectrometry (ICP-OES).
[0065] According to one embodiment, the alkali metal may be sodium or potassium, and sodium may be preferred in view of excellent improving effects.
[0066] As described above, since the content ratio of phosphorus, calcium and alkali metal on the catalyst surface and the entire surface is controlled within an optimized range, the catalyst according to the present disclosure can simultaneously achieve high selectivity and high conversion rate when preparing unsaturated carboxylic acid or its derivatives.
[0067] According to one embodiment, the apparent density of the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 0.8 g / cm 3 To about 1.0g / cm 3 When the density is too low, a side reaction caused by catalyst breakage during the dehydration reaction may occur due to the weak strength of the catalyst, and there may be a problem of increased pressure difference inside the reactor. When the density is too high, there may be a problem of reduced specific surface area.
[0068] According to one embodiment, the crush strength value of the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 6N to about 20N. In other words, the catalyst according to one embodiment of the present disclosure has a very excellent crush strength value, and therefore, even when the catalyst is loaded in a reactor and exposed to severe reaction conditions, the catalyst is not easily broken, thereby maintaining the loading state in the initial state.
[0069] According to one embodiment, the specific surface area value of the catalyst used for the dehydration reaction of hydroxypropionic acid and its derivatives may be about 50 m 2 / g to about 90m 2 / g, or about 50m 2 / g or above, or about 55m 2 / g or above, or about 60m 2 / g or more, and about 90m 2 / g or less, or about 85m 2 / g or less, indicating that it can have a wide specific surface area.
[0070] In addition, the catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives can have a P value represented by the following equation 1 of about 3.5 to about 19, about 3.5 or more, or about 4.0 or more, or about 5.0 or more, or 6.0 or more, about 19 or less, or about 17 or less, or about 15 or less, or about 12 or less, or about 10 or less.
[0071] [Equation 1]
[0072] P=A*B / C
[0073] In equation 1, A represents the volume average particle size (μm) of the powder, B represents the crushing strength (N), and C represents the specific surface area (m 2 / g) value.
[0074] Equation 1 represents parameterization of factors that directly affect the strength of a catalyst formed by molding a primary particle powder. When the parameter value is too large or too small, the catalyst deactivation time may be shortened, which may cause problems such as deterioration of catalyst performance and long-term stability.
[0075] In addition, according to another aspect of the present disclosure, a method for preparing a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives is provided, the method comprising the following steps: preparing a slurry by introducing 1 to 50 parts by weight of a binder relative to 100 parts by weight of hydroxyapatite; producing a molded body by molding the slurry; and drying the molded body.
[0076] According to one embodiment, the preparation method may further include the step of grinding the hydroxyapatite before introducing the binder.
[0077] In terms of controlling the particle size of the ground powder to be produced, that is, the volume average particle size of the primary particles, a grinder such as a jet mill or a pin mill or the like may be preferably used for grinding.
[0078] The adhesive may contain water or an alcoholic solvent (excluding isopropyl alcohol) and isopropyl alcohol as an adhesive component.
[0079] According to one embodiment, the amount of the binder may be about 1 part by weight or more, or about 5 parts by weight or more, or about 10 parts by weight or more, and about 70 parts by weight or less, or about 60 parts by weight or less, or about 50 parts by weight or less, relative to 100 parts by weight of hydroxyapatite.
[0080] When the amount of the binder used is too small or too large, there may be problems in that molding properties may be deteriorated during the preparation of the catalyst and the strength of the catalyst to be prepared may be deteriorated.
[0081] However, the content of the binder may vary depending on molding conditions such as particle size of particles, drying temperature, drying time, and the like.
[0082] In addition, the adhesive may include about 0.1 parts by weight or more, or about 1 part by weight or more, or about 3 parts by weight or more, and about 10 parts by weight or less, or about 9 parts by weight or less, or about 8 parts by weight or less of isopropyl alcohol.
[0083] When the content of isopropyl alcohol is too low or too high, there may be a problem that the strength of the catalyst to be prepared may be deteriorated or the specific surface area may be reduced.
[0084] In the step of preparing the slurry by introducing the binder into the hydroxyapatite powder and then mixing them, there is no particular limitation on the mixing method and the like.
[0085] In addition, when a molded body is produced by molding the slurry, a molding method using an extruder or the like can be preferably used.
[0086] Thereafter, the molded body formed into pellets or the like is dried. In the drying step, the drying may be performed at about 10° C. or more, or about 20° C. or more, and about 120° C. or less, or about 110° C., for about 30 minutes to about 24 hours.
[0087] According to one embodiment, a step of calcining the dried catalyst may be further included.
[0088] Meanwhile, the present disclosure provides a method for preparing acrylic acid, which comprises the step of carrying out a dehydration reaction of a hydroxycarboxylic acid or a derivative thereof in the presence of the above catalyst.
[0089] Meanwhile, the present disclosure provides a method for preparing unsaturated carboxylic acid and its derivatives using the catalyst.
[0090] Specifically, the preparation method includes the step of performing a dehydration reaction of a hydroxycarboxylic acid or a derivative thereof in the presence of the catalyst for preparing an unsaturated carboxylic acid or a derivative thereof.
[0091] In the method for preparing unsaturated carboxylic acids and derivatives thereof according to the present disclosure, specific examples of hydroxycarboxylic acids as raw materials may include lactic acid, citric acid, 3-hydroxypropionic acid, 3-hydroxy-2-methylpropionic acid, 3-hydroxybutyric acid, 3-hydroxy-2-methylbutyric acid, 2,3-dimethyl-3-hydroxybutyric acid, and the like, as well as salts, esters or dimers thereof, and the like.
[0092] The hydroxycarboxylic acid or its derivative can be used in the form of an aqueous solution dissolved in water, or in the form of a solution dissolved in a mixed solvent of a hydrophilic organic solvent (such as alcohol or ether) and water.
[0093] In this regard, the concentration of the hydroxycarboxylic acid or its derivative is not particularly limited, but may be 20% by weight or more, or 60% by weight or less in consideration of efficiency.
[0094] In addition, the amount of the catalyst used in the dehydration reaction can be appropriately selected by considering the type of reactants, reaction time, etc. For example, the introduction amount of the hydroxycarboxylic acid or its derivative may be 0.05 g or more and 3 g or less per hour, more specifically, 0.1 g or more and 1 g or less per hour, or 0.5 g or less per hour, based on 1 g of the catalyst.
[0095] In addition, the dehydration reaction can be carried out by a continuous reaction using a fixed bed reactor, or by a batch reaction. More specifically, the dehydration reaction can be carried out by a continuous reaction, wherein the catalyst is loaded in a fixed bed reactor, and by continuously introducing reactants into the reactor to react them, thereby continuously preparing the product.
[0096] In the continuous reaction process using a fixed bed reactor, an inert gas such as nitrogen, argon or helium can be used as a carrier gas. There is no particular limitation on the input amount of the carrier gas, and it can be appropriately determined according to the reaction conditions such as the input amount of the reactants. For example, the introduction amount of the carrier gas can be more than 5 ml / min or less than 500 ml / min per 1 g of the catalyst.
[0097] In addition, the dehydration reaction can be carried out at a temperature of 300°C or more and 500°C or less, more specifically, at a temperature of 300°C or more, 350°C or more, or 360°C or more, and 500°C or less, 450°C or less, or 380°C or less.
[0098] In addition, the dehydration reaction can be carried out at a pressure of more than 0.5 bar and less than 5 bar, more specifically, at a pressure of more than 0.5 bar, or more than 0.8 bar, and less than 5 bar, or less than 2 bar, and more specifically, under normal pressure (1±0.2 bar).
[0099] In addition, the reactant hydroxycarboxylic acid or its derivative can be used at 0.05h -1 Above, 3h -1 The following mass space velocity (WHSV) was introduced, more specifically, at 0.05 h -1 Above, or 0.1h -1 More than, or 0.3h -1 More than 3 hours -1 Less than or 1h -1 Less or 0.8h-1 The following WHSV is introduced.
[0100] When the reaction temperature is higher than 500 °C, or the reaction pressure is lower than 0.5 bar, or the reactant supply rate WHSV is lower than 0.1h -1 When the reaction temperature is lower than 300 °C, the reaction pressure is higher than 5 bar, or the reactant supply rate WHSV is higher than 1 h -1 When the reaction temperature is too low, the conversion rate may be reduced, and thus other reaction conditions may have to be drastically increased, resulting in a shortened catalyst life and increased costs for the steps of separating and recovering the products.
[0101] By the dehydration reaction as described above, at least a part of the hydroxycarboxylic acid or its derivative is converted into an unsaturated carboxylic acid or its derivative.
[0102] The method for preparing an unsaturated carboxylic acid or a derivative thereof according to the present disclosure improves the conversion rate of the unsaturated carboxylic acid by using the above catalyst, thereby preparing the unsaturated carboxylic acid and the derivative thereof with high yield.
[0103] Beneficial Effects
[0104] The catalyst according to one embodiment of the present disclosure has very excellent life characteristics while having high reaction yield and selectivity. DETAILED DESCRIPTION
[0105] Hereinafter, the functions and effects of the present invention will be described in more detail with reference to specific embodiments of the present invention. However, these embodiments are provided only to illustrate the present invention, but the scope of the present invention is not limited thereby.
[0106] <Example>
[0107] Catalyst preparation
[0108] Example 1
[0109] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0110] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0111] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 26 μm.
[0112] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 60° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0113] Example 2
[0114] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0115] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0116] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 42 μm.
[0117] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 60° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0118] Example 3
[0119] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0120] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0121] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 60 μm.
[0122] With respect to 100 parts by weight of the obtained particles, 25 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 30° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0123] Example 4
[0124] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0125] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0126] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 80 μm.
[0127] With respect to 100 parts by weight of the obtained particles, 35 parts by weight of water and 5 parts by weight of isopropyl alcohol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 100° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0128] Example 5
[0129] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0130] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0131] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 90 μm.
[0132] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 70° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0133] Comparative Example 1
[0134] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0135] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0136] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 12 μm.
[0137] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 120° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0138] Comparative Example 2
[0139] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0140] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0141] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 8 μm.
[0142] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 5 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 60° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0143] Comparative Example 3
[0144] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0145] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0146] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 160 μm.
[0147] With respect to 100 parts by weight of the obtained particles, 28 parts by weight of water and 10 parts by weight of isopropanol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 60° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0148] Comparative Example 4
[0149] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0150] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0151] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 220 μm.
[0152] 35 parts by weight of water was added as a binder relative to 100 parts by weight of the obtained particles, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared using an extruder. The pellets were dried at about 150° C. for about 12 hours to obtain a catalyst molded body in the form of solid pellets.
[0153] Comparative Example 5
[0154] 35 g of HAP and 65 g of CaPP were mixed and placed in a high temperature and high pressure reactor, and then 500 ml of 1 M NaOH solution was introduced and reacted at 150° C. and 5 atm for 4 hours. The obtained white precipitate was filtered and washed to obtain a powdered Na-HAP component catalyst (yield: 90%).
[0155] The powdered catalyst thus obtained is finely ground using a jet mill or a pin mill. During the grinding process, the particle size of the prepared particles is controlled by changing the conditions of the grinder.
[0156] The particle size was measured using a wet particle size distribution (PSD) analyzer (Microtrac S3500), and the volume average particle size was found to be about 500 μm.
[0157] With respect to 100 parts by weight of the obtained particles, 25 parts by weight of water and 8 parts by weight of isopropyl alcohol were added as a binder, followed by sufficient mixing, and then pellets having a size of about 2.5 mm were prepared, but molding failed.
[0158] Measurement of crushing strength
[0159] The crush strength of individual pellets was measured using a strength tester according to ASTM D4179.
[0160] Density measurement
[0161] The tap density was measured using a COPLEY tap density tester with the same number of taps.
[0162] Measurement of specific surface area
[0163] The specific surface area of the catalyst was calculated based on the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mino II from BEL, Japan.
[0164] Advances in lactic acid dehydration reactions
[0165] About 0.71 g of the catalyst prepared in Preparation Example 1 was charged into a fixed bed reactor and heated for 0.67 h at a reaction temperature of 370° C. and normal pressure (1±0.2 bar). -1The WHSV was supplied with a 30 wt % aqueous lactic acid solution to carry out the dehydration reaction.
[0166] The reaction product was received and removed during the initial 4 hours of the reaction (reaction stabilization time), and then the liquid product obtained in 2 hours was recovered as a liquid sample using a 4° C. cooling collector while the reaction was continuously performed.
[0167] The recovery rate of acrylic acid was monitored, and the point at which the recovery rate showed a maximum value was identified, indicating that the reaction was activated. Then, based on the time of 24 hours, the time at which the recovery rate decreased by 10% from the reference value was determined as the catalyst deactivation time.
[0168] The measurement results are summarized in the table below.
[0169] [Table 1]
[0170]
[0171] (*) A represents particle size, B represents crushing strength, and C represents specific surface area.
[0172] Referring to the above table, some comparative examples show that the deactivation time reaches a certain level. However, in these cases, the strength is significantly reduced. When the crushing strength of the catalyst is low, as shown in these comparative examples, the catalyst molded body located below the catalyst packing layer is crushed by the high load as the reaction proceeds, and eventually, the catalyst packing layer cannot maintain its shape, thereby impairing the long-term stability of the reaction.
[0173] In contrast, it can be confirmed that the catalyst according to the example of the present invention has a wide specific surface area and at the same time has a very high crush strength, and its long-term stability is very excellent, which can be inferred from the deactivation time.
Claims
1. A catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives, the catalyst comprising a shaped body in which hydroxyapatite primary particles are aggregated, wherein: The volume average particle size of the primary particles is 15 μm to 150 μm; and the P value represented by the following equation 1 is 3.5 to 19: [Equation 1] P=A*B / C In equation 1, A represents the volume average particle size (μm) of the powder, B represents the crushing strength (N), and C represents the specific surface area (m 2 / g) value.
2. The catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives according to claim 1, wherein The volume average particle diameter of the primary particles is 25 μm to 100 μm.
3. The catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives according to claim 1, wherein The alkali metal content of the catalyst is 3 to 8 wt %.
4. The catalyst for dehydration reaction of hydroxypropionic acid and its derivatives according to claim 3, wherein The alkali metal is sodium or potassium.
5. The catalyst for dehydration reaction of hydroxypropionic acid and its derivatives according to claim 1, wherein The apparent density of the catalyst is 0.8 g / cm 3 Up to 1.0g / cm 3 .
6. The catalyst for dehydration reaction of hydroxypropionic acid and its derivatives according to claim 1, wherein The catalyst has a crush strength value of 6N to 20N.
7. The catalyst for dehydration reaction of hydroxypropionic acid and its derivatives according to claim 1, wherein The specific surface area of the catalyst is 50 m 2 / g to 90m 2 / g.
8. A method for preparing a catalyst for the dehydration reaction of hydroxypropionic acid and its derivatives, the method comprising the following steps: The slurry is prepared by introducing 1 to 50 parts by weight of a binder relative to 100 parts by weight of hydroxyapatite; producing a shaped body by shaping the slurry; and The shaped body is dried.
9. The method according to claim 8, wherein: The binder includes 0.1 parts by weight to 10 parts by weight of isopropyl alcohol relative to 100 parts by weight of hydroxyapatite.
10. A method for preparing acrylic acid, comprising the step of carrying out a dehydration reaction of a hydroxycarboxylic acid or a derivative thereof in the presence of the catalyst according to claim 1.
Citation Information
Patent Citations
Four directions high place working vehicles
KR1020230081445A
Method for synthesizing unsaturated carboxylic acid and / or derivative of same
WO2011052178A1